Case Report of Probable DRESS Syndrome Associated with Ribociclib - Florian Carneiro; Marine Bove; Frédérique Beau-Salinas; Tevy San; Pierre Combe (Case Reports in Oncological Medicine)
Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare but known and potentially severe side effect of drugs. The recent development of cyclin-dependent kinase 4/6 (CDK4/6) inhibitors, such as ribociclib, has considerably improved the management of hormone receptor positive (HR+) and HER2 negative (HER2-) advanced breast cancer. Here, we present the case of an 83-year-old patient who developed a probable DRESS syndrome induced by ribociclib, presenting with fever, eosinophilia, rash, and hepatic cytolysis. The RegiSCAR score was 4. The symptomatology evolved favorably with topical and systemic corticosteroids, without any sequel. Another CDK4/6 inhibitor, palbociclib, was introduced later without any cross-toxicity and with an excellent therapeutic response for more than 3 years.